Algoritme penggantian cache proxy terdistribusi untuk meningkatkan kinerja server web - Marvin Chandra Wijaya (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2020)
The performance of web processing needs to increase to meet the growth of internet usage, one of which is by using cache on the web proxy server. This study examines the implementation of the proxy cache replacement algorithm to increase cache hits in the proxy server. The study was conducted by creating a clustered or distributed web server system using eight web server nodes. The system was able to provide increased latency by 90 % better and increased throughput of 5.33 times better.